Frequency-Dependent Dielectric Properties of Agricultural Soils from Buldhana District, Maharashtra - Choundiye, Shrikant; Saindar, Shrinivas; Deshmukh, Sushant; Mahajan, Chandrakant (International Journal of Aquatic Research and Environmental Studies, 2026)
Soils are heterogeneous dielectric materials, and their response to microwave radiation depends on texture, packing, organic matter, mineral composition, pore space, chemical environment, and frequency. A reliable local dielectric database is therefore useful for microwave soil studies, electromagnetic modelling, and remote-sensing interpretation. In the present work, ten surface soil samples collected from agricultural locations of Buldhana District, Maharashtra, India, were characterized at three microwave frequencies: C-band (4.7 GHz), J-band (5.8 GHz), and X-band (9.68 GHz). The measurements were performed using a klystron-based rectangular waveguide bench operated in the dominant TE10 mode, and the dielectric constant was evaluated by the VSWR double minima method. In addition to microwave measurements, each soil sample was analysed for particle-size distribution, soil texture, pH, alkalinity, soil organic carbon, available major nutrients, calcium carbonate, and selected micronutrients. The measured dielectric constant ranged from 3.4601 to 4.9611 at C-band, 3.0238 to 3.8104 at J-band, and 1.8840 to 2.8970 at X-band. A clear decrease in dielectric constant with increasing frequency was observed for all samples. The average dielectric constant decreased from 4.0309 at 4.7 GHz to 2.3849 at 9.68 GHz, corresponding to an average reduction of about 40.33%. The results show that the microwave behaviour of Buldhana soils cannot be explained by a single soil property alone. Texture, organic carbon, exchangeable ions, calcium carbonate, and sample packing together influence the observed response. The study provides an experimentally measured dielectric dataset for Buldhana soils and demonstrates the suitability of the TE10 waveguide double-minima technique for comparative characterization of air-dried granular soils.